Dynamic adaptation of phytoplankton vertical migration to changing grazing and nutrient conditions - Salonen, Kalevi (Springer, 2025)
Despite the ubiquitous occurrence of vertical migration of phytoplankton its quantitative significance remains poorly known. We eliminated a dense Daphnia population in a pond by introducing whitefish fingerlings, and assessed the effects on the vertical migration of dominating motile phytoplankton. At the highest abundance of Daphnia, cryptophytes reduced grazing losses by staying in the hypolimnion day and night, but Mallomonas species armoured by silica bristles remained in the epilimnion. After the fish introduction, phytoplankton was released from Daphnia grazing pressure, allowing cryptophytes to occur in the epilimnion also at noon. At the same time, increased phytoplankton biomass exacerbated the nutrient depletion. Cryptophytes compensated for that by migrating into the anoxic hypolimnion, whereupon their growth rates increased. The collapse of Daphnia was also associated with a temporary increase in nutrient regeneration by enzyme activities and decreases in total nutrient concentration and bacterial biomass in the whole water column. Our results show that cryptophytes can dynamically modify their vertical migration to balance between the exploitation of various nutrient resources and the risk of becoming eaten. Hypolimnetic nutrient resources can be quantitatively more important for phytoplankton than previously assumed.